2009
DOI: 10.1637/8521-111908-case.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Atherosclerosis by Histochemical and Immunohistochemical Methods in African Grey Parrots (Psittacus erithacus) and Amazon Parrots (Amazona spp.)

Abstract: The aim of the study was to characterize atherosclerotic changes in African grey parrots (Psittacus erithacus) and Amazon parrots (Amazona spp.) by histochemical and immunohistochemical methods. Samples of the aorta ascendens and trunci brachiocephalici from 62 African grey parrots and 35 Amazon parrots were stained by hematoxylin and eosin and Elastica van Gieson for grading of atherosclerosis in these birds. Four different stages were differentiated. The incidence of atherosclerosis in the examined parrots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 37 publications
2
60
0
3
Order By: Relevance
“…In birds, particularly the pigeon, similar pathological and ultrastructural studies have been performed and lead to similar findings (Lauper et al, 1975;Hansen, 1977;Stout & Thorpe, 1980;Barr et al, 1991;Casale et al, 1992). Recent studies have evaluated the characteristics of psittacine atherosclerosis using histopathology and IHC (Bavelaar & Beynen, 2003;Krautwald-Junghanns et al, 2004;Schenker & Hoop, 2007;Fricke et al, 2009). However, there are some limitations to light microscopy alone in describing atherosclerotic lesions such as difficulties in characterizing cell types, describing the fine structure of the atherosclerotic plaques, and quantifying the lesion composition.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…In birds, particularly the pigeon, similar pathological and ultrastructural studies have been performed and lead to similar findings (Lauper et al, 1975;Hansen, 1977;Stout & Thorpe, 1980;Barr et al, 1991;Casale et al, 1992). Recent studies have evaluated the characteristics of psittacine atherosclerosis using histopathology and IHC (Bavelaar & Beynen, 2003;Krautwald-Junghanns et al, 2004;Schenker & Hoop, 2007;Fricke et al, 2009). However, there are some limitations to light microscopy alone in describing atherosclerotic lesions such as difficulties in characterizing cell types, describing the fine structure of the atherosclerotic plaques, and quantifying the lesion composition.…”
Section: Introductionmentioning
confidence: 86%
“…The prevalence of atherosclerosis in psittacines, reported from post-mortem surveys, ranges from 2.6 to 91.8% depending on the geographical areas, the time span of the study, the species, and the inclusion criteria (Garner & Raymond 2003;Bavelaar & Beynen, 2004;KrautwaldJunghanns et al, 2004;Fricke et al, 2009). Prevalences by age groups are unknown but the prevalence and severity of the lesions appear increased in older psittacine birds (Bavelaar & Beynen, 2004;Fricke et al, 2009). All psittacine species appear susceptible but the disease is most frequently reported in Amazon parrots (-Amazona spp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, immunization with turkey herpesvirus vaccine or SB -1 vaccine prevented atherosclerotic lesions. Hajjar et al [103] demonstrated histologically that infection of normocholesterolemic, specific-pathogen-free chickens with Marek's disease herpesvirus (MDV) lead to chronic atherosclerosis like that in humans (Figures 2 and 3). …”
Section: Birdsmentioning
confidence: 99%